PERLINDUNGAN ANAK DALAM PROSES PERADILAN PIDANA - Fitra Oktoriny (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
Criminal Justice Process Children in certain cases are often unable to develop their rights, it is necessary to receive assistance and protection in exercising their rights and obligations in a balanced and humane way, including pedampingan, inclusion of supervision, prevention and not ignore the mental aspects, physical social of a child. The Criminal Justice System of the Child through the judicial process that in providing child protection should pay more attention to the rights of the child.